PERUBAHAN GARIS PANTAI DI PERAIRAN MUARA BANYUASIN KAITANNYA DENGAN SEDIMENTASI - Pratama, M. Andrian Putra; Barus, Beta Susanto; Putri, Wike Ayu Eka (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2020)
The estuary waters of the Banyuasin River are one of the river estuary waters that is affected by the sedimentation process. This area gets a big influence from land input. This study aims to analyze the changes in the coastline in Muara Banyuasin Waters, South Sumatra associated with sediment characteristics and sedimentation rates. This research was conducted in October 2018 and sampling was carried out by installing sediment traps for 14 days. Samples were taken once a week and then the rate of sediment accumulation were calculated. Analysis of coastline changes is done using image data processing with a span of 5 years using ErMapper 7.0 software. The results of image data processing are discussed descriptively with sedimentation rates and sediment characteristics. The results showed that the predominant characteristics of sediments were clay and silt with sediment accumulation rates ranging from 2.06 kg/m2/day-6.55 kg/m2/day. The estuary waters of the Banyuasin River undergo a change in coastline in the form of sedimentation and abrasion. Sedimentation occurred at 6 stations while abrasion occurred at 2 stations. Coastline changes are ranged ±33 m-±322 m. Stations that experience high coastline changes are characterized by high sedimentation rates and subtle dominant substrate types (silty clay). Whereas areas that experience low coastline changes have low sedimentation rates with coarser substrate types (sandy silt).